Standing on the shoulders of giants : traditions and innovations in research methodology - Boyd, Brian; Crook, T. Russell; Lê, Jane K.; Smith, Anne D. (Bingley, U.K. : Emerald Publishing Limited, 2019)
The latest volume of the Research Methodology in Strategy and Management series uncovers theoretical developments in management and strategy, highlighting how firms succeed today, as well as offering cutting edge thinking on new and evolving research methods to study organizations.Standing on the Shoulders of Giants: Traditions and Innovations in Research Methodology collates a wide range of perspectives on strategy and management and introduces new approaches to researching organizations. Two retrospective accounts from Kathy Eisenhardt and Denny Gioia provide contextual balance to the subsequent chapters which explore various research methodologies, including: qualitative comparative analysis, videometric methods, modes of process research, visual research methods and qualitative research in strategy. This culminates in a useful how-to guide which builds on insights about teaching aspiring entrepreneurs with a "canvas" and provides researchers with a canvas to design and execute high quality projects. This is an illuminating guide book for all academics and researchers working in the fields of management, strategy, international business, entrepreneurship and organization theory, interested in starting research projects.
Prelims -- Why research methodology in strategy and management remains as important as ever -- Thoughts about research, inspirations for research and future research -- If i had a magic wand: reflections on developing a systematic approach to qualitative research -- Videometric measurement of individual characteristics in difficult to access subject pools: demonstrating with Ceos -- The research design canvas: a tool for creating better studies -- How visual methods can enhance our understanding of strategy and management -- Performing process research -- An integrative review of qualitative strategy research: presenting 12 "designs-in-use" -- Qualitative comparative analysis in entrepreneurship: exploring the approach and noting opportunities for the future -- Index.
Includes index.
Print version record
Keywords: Management -- Research; Qualitative research; Research -- Methodology; Business & Economics -- Research & Development; Research & development management